Difficulties of primary diagnosis in patients with suspected systemic mastocytosis - Z. K. Abdulkhalikova; M. V. Barabanshchikova; V. V. Baykov; I. M. Barkhatov; E. V. Morozova; I. S. Moiseev (Онкогематология, 2024)
Background. Mastocytosis is a rare myeloproliferative disease based on clonal hematopoiesis of mast cells, with accumulation of mast cells in various tissues and organs. The cutaneous mastocytosis is common in the pediatric population and, in general, progression to aggressive forms is not typical. In the adult population, there is systemic mastocytosis with a predominance of indolent and smoldering forms according to the literature, but there aren’t epidemiological data for the Russian Federation.Aim. To evaluate the results of primary diagnostics obtained during the examination of 70 patients with suspected systemic mastocytosis.Materials and methods. The histological studies of the skin and bone marrow, mutations in the c-kit gene in the bone marrow and serum tryptase level were examined in the Raisa Gorbacheva Memorial Research Institute for Pediatric Oncology, Hematology and Transplantation in accordance with WHO 2017 criteria.Results. The diagnostic results of 70 patients with suspected mastocytosis, the diagnosis was confirmed in 71.4 % (n = 50) of patients, of which systemic mastocytosis accounted for 82 % (n = 41). The 2 most common categories were identified: indolent systemic mastocytosis in 23 (56 %) patients and widespread forms in 15 (36.5 %), with a median time of diagnosis of 12 and 5 years, respectively.Conclusion. The late diagnosis is noted in all subgroups of systemic mastocytosis.